Thursday

April 17, 2014

April 17, 2014

Posted by **Juan** on Monday, February 1, 2010 at 11:08pm.

- alg math 116 -
**PsyDAG**, Tuesday, February 2, 2010 at 9:01amy = 39 + 5x

9x + 3y = -51

Substitute 39 + 5x for y in the second equation and solve for x. Put that value in the first equation to solve for y. Check by putting both values in the second equation.

I hope this helps.

**Related Questions**

Math - Solve using the substitution method -x-3y=-20 5x+3y=40

math - 9x+3= -66 5x-3y= -60 solve using elimination method?

algebra - Solve using the substitution method. State if there are infinite ...

MATH - Solve system of equations algebraically. 1. 3x-3y=24 and 2x+5y=-37 2. -9x...

substitution method - solve using the substitution method 8x+6y=8 -9x+y=22 The ...

alg 1 - use the method of substitution to solve the system of linear equation 2x...

algebra - use the Substitution Method. Please give it a try. y = 3x + 4 5x + 3y...

math - Solve by substitution method 9x+6y=21-9x+y=35 What is the solution of the...

substitution method - solve using the substitution method 6x+2y=-14 -5x+y=25 The...

substitution method - solve using the substitution method 8x -9y= -95 5x+64=y ...